2014
DOI: 10.1115/1.4027663
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Anisotropy of Human Lumbar Vertebral Trabecular Bone on Quantitative Computed Tomography-Based Apparent Density

Abstract: Most studies investigating human lumbar vertebral trabecular bone (HVTB) mechanical property-density relationships have presented results for the superior-inferior (SI), or "on-axis" direction. Equivalent, directly measured data from mechanical testing in the transverse (TR) direction are sparse and quantitative computed tomography (QCT) density-dependent variations in the anisotropy ratio of HVTB have not been adequately studied. The current study aimed to investigate the dependence of HVTB mechanical anisotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Elastic modulus obtained in our studies were similar to former experimental compression studies on trabecular bone samples (18,19). Compression tests on vertebral trabecular bone cores have shown that the apparent elastic modulus on axial direction was 189.7 MPa (18), which is simular to the value of 139.96-146.…”
Section: Discussionsupporting
confidence: 88%
“…Elastic modulus obtained in our studies were similar to former experimental compression studies on trabecular bone samples (18,19). Compression tests on vertebral trabecular bone cores have shown that the apparent elastic modulus on axial direction was 189.7 MPa (18), which is simular to the value of 139.96-146.…”
Section: Discussionsupporting
confidence: 88%
“…Six studies used dried specimens in the compression test. 33 , 51 , 135 , 138 , 157 , 158 The majority of studies tested bone specimens in unconfined conditions, but some tested in confined conditions using confinement chambers, 22 , 98 , 159 , 160 a steel annulus, 52 or polytetrafluoroethylene (PTFE) tape. 130 …”
Section: Resultsmentioning
confidence: 99%
“…Potential sources of error in compression testing of trabecular bone include machine compliance, end artifacts and side artifacts [34, 6466]. Several steps in the mechanical testing procedure were designed to reduce these errors and sources of variance.…”
Section: Discussionmentioning
confidence: 99%
“…Standard ZETOS specimen dimensions (10 mm diameter, 5 mm height) meet the main goal of maintaining core viability for several weeks [9, 30], and are adequate for continuum assumptions [34, 6466] as required for equations of Hooke’s Law. The aspect ratio of the bone cores (0.5) although favorable for maintaining viability could increase end artifacts in the measurement of E app because of specimen-platen interface conditions and structural end artifacts [34, 6466]. The F-δ curves (Figure 2) did not reveal a large “toe” region indicating machine compliance and possible end-artifact errors have been minimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation